Numerical analyses of MILD and conventional combustions with the Eddy Dissipation Concept (EDC). (15th December 2021) - Kuang, Yucheng; He, Boshu; Wang, Chaojun; Tong, Wenxiao; He, Di
Abstract: Moderate or intensive low-oxygen dilution (MILD) combustion is a novel combustion technology with high efficiency and low emissions. The turbulence-chemistry interaction is crucial in the numerical research of MILD combustion. In this paper, the MILD and conventional combustions are investigated numerically with the original and the modified Eddy Dissipation Concept (EDC) parameters. The results show that the original EDC constants are suitable for conventional combustion prediction. While, the predicted temperature, and therefore the NO x production in MILD combustion, are overestimated with the original EDC constants. MILD combustion can be reasonably predicted with the modified EDC constants. However, it is worth noting that, the numerical results of conventional combustion with the modified EDC parameters are similar to those of MILD combustion, so it is difficult to judge whether the combustion mode is MILD combustion only with the numerical results at this state. In addition, although conventional combustion with the modified EDC parameters is incorrectly predicted for the distributions of temperature and species, the flow field is basically unchanged with different EDC parameters. Therefore, the flow characteristics can be used to numerically distinguish between MILD combustion and conventional combustion. Highlights: The effects of EDC parameters on MILD or conventional combustion are studied. Default EDC parameters are suitable for conventional combustion. MILD combustion can be correctly predicted with modified EDC parameters. Conventional combustion cannot be correctly predicted with modified EDC parameters.